Investigating the genetic interaction between DNA replication proteins Mcm10 and RecQ4 in Drosophila melanogaster - Knuckles, Christopher I (East Carolina University, 2017)
Necessary to the survival of cellular life is proper replication and maintenance of the genome. Replication proteins Mcm10 and RecQ4 have well-characterized essential roles in assembly, initiation, proper functioning of the eukaryotic replication machinery, and genome stability. Mcm10 enables efficient assembly of the pre-replication complex while RecQ4 delivers essential proteins forming that complex; both of which are pivotal for origin firing. Recent studies suggest that Mcm10 is not required for RecQ4 chromatin localization or association with the CMG complex, conflicting with a previous report that Mcm10 mediates the interaction between RecQ4 and Mcm2-7 in an S-CDK dependent manner. We have found that a homozygous mutation of RecQ4 is lethal in fruit flies unless they possess a C-terminal domain (CTD) truncation of Mcm10, suggesting that Mcm10 and RecQ4 exhibit a genetic interaction. Here, we investigate how an Mcm10/RecQ4 genetic interaction might be important for organism viability and to facilitate critical replication states - like those found in larval brain development and adult oogenesis. We also investigate the individual and combined roles of Mcm10 and RecQ4 in genome stability. The Mcm10 CTD truncation rescue of lethal RecQ4 phenotypes can reveal much about how the cooperative roles of these proteins affect DNA replication and responses to DNA damage, but this requires further investigation. Our research aims to explore the nature of the Mcm10/RecQ4 genetic interaction by conducting genetic investigations, proliferation assays, and double strand break (DSB) studies in the Drosophila larval brain and adult ovary. We propose that Mcm10 and RecQ4 genetically interact to facilitate DNA replication and genome stability in Drosophila melanogaster.
Keywords: Mcm10; RecQ4; DNA replication; Chromosomal proteins; Drosophila melanogaster; DNA damage